Розвиток криміналістичних знань про економічну злочинність у сфері банківської діяльності - Корнієнко, В.В.; Korniienko, V.V.; ORCID: http://orcid.org/0000-0002-7682-1281 (Вісник Харківського національного університету внутрішніх справ. - 2017. - № 2 (77). - С. 63-73, 2017)
Розглянуто етапи розвитку криміналістичного забезпечення протидії економічній злочинності в банківській сфері. Проаналізовано взаємозв’язок між злочинною діяльністю в цій сфері та рівнем розвитку криміналістичних знань.

The article analyzes knowledge about criminal investigation of crimes in the banking sector. Author divided these special knowledge into several stages from appearance of the first studies about investigation malfeasance in the economic sphere (50th of the XX c.) and up to nowadays. It was observed that the progress of knowledge significantly lagged behind degree of criminality in the banking sphere. This gap is can be explained due primarily to the lack of an integrated approach in studying of economic crimes. The state of countering these crimes objectively has such challenges as: legislation, current reforms, lack of experience and specialized trainings, etc. It’s mean lack of special knowledge in the field of economics, accounting, financial analysis and banking. The criminalistics science need in the predictive function today. It will help in developing methods for a timely response to the new challenges of crime in the banking business and in other spheres. This will prevent large-scale damage caused by criminal activity as well as greatly saves procedural costs in late responding to crimes.

Рассмотрены этапы развития криминалистического обеспечения противодействия экономической преступности в банковской сфере. Проанализирована взаимосвязь между преступной деятельностью в этой сфере и уровнем развития криминалистических знаний.
The development of knowledge in the banking crimes sphere
Развитие криминалистических знаний об экономической преступности в сфере банковской деятельности
Корнієнко, В. В. Розвиток криміналістичних знань про економічну злочинність у сфері банківської діяльності / В. В. Корнієнко // Вісник Харківського національного університету внутрішніх справ. - 2017. - Вип. 2. - С. 63-73.
Корнієнко В. В. "Розвиток криміналістичних знань про економічну злочинність у сфері банківської діяльності." Вісник Харківського національного університету внутрішніх справ 2 (2017): 63-73.
Korniienko, V.V. (2017), “The development of knowledge in the banking crimes sphere” [Rozvytok kryminalistychnykh znan pro ekonomichnu zlochynnist u sferi bankivskoi diialnosti], Visnyk Kharkivskoho Natsionalnoho Universytetu Vnutrishnikh Sprav, No. 2, pp. 63–73.
Keywords: Криміналістика. Criminalistics. Криминалистика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; криміналістичні знання; злочинна діяльність; злочинність у банківській сфері; економічна злочинність; банківська діяльність; spesial knowledge in criminal investigation; criminal activity; banking sector; banking; economic crimes; scientific research; криминалистические знания; преступная деятельность; банковская сфера; банковская деятельность; экономическая преступность